Perbedaan Kebocoran Mikro Antara Hasil Aplikasi Surface Sealant dan One-Step Self-Etch Adhesive Pasca Penumpatan Resin Komposit Kelas V - Jonathan Morgan Sudjaka; Juanita Amaludin Gunawan; Taufiq Ariwibowo (Jurnal Material Kedokteran Gigi, 2021)
Microleakage is one of the major problems in the successful of a composite resin restoration. The application of coating materials using surface sealant or re-bonding using bonding agent to the surface of the restoration is a method to reduce the occurrence of microleakage. The aim of this study is to determine the differences in microleakage between the application of surface sealant and one-step self-etch adhesive after composite resin restoration on class V cavities. Twenty-one lower premolar teeth were randomly selected and then divided into two treatment groups that consist ten samples for each group and one sample as control. Group I: Surface sealant (G-Coat Plus), group II: One-step self-adhesive (OptiBondTM All-In-OneTM Kerr), and the control group was not given any coating materials. All samples were prepared in the buccal surface with a size of 3 mm occlusal-gingival, 3 mm mesial-distal, and 1.5 mm cavity depth. After applied coating materials for all treatment groups, all samples including control group are smeared with nail coloring on the crown and apex, except the surface of the restoration until 1 mm around the restoration. Samples were then immersed in artificial saliva for 24 hours, followed by immersion in methylene blue for the next 24 hours. The teeth are cut in a buccal-lingual direction and then observed the penetration depth of methylene blue under a stereo microscope using 20x magnification. Statistical analysis using Mann-Whitney test between two treatment groups (p<0.05). The results of this study indicate that group I has less microleakage than group II. The conclusion of this study is that there are differences in microleakage between the application of surface sealants and one-step self-etch adhesive after composite resin restoration on class V cavities.